ADP-ribosylation of host cell proteins in salmonella infection - Pinto, Rita Gil Fernandes (2019)
ADP-ribosylation is a reversible enzymatic post-translational modification consisting in the transfer of one or many ADP-ribose residues from NAD+ to a target protein. ADPribosylation signalling has been linked to cancer and immune responses. Many bacterial protein toxins have been identified to act through ADP-ribosylation of protein targets inside the host cell. This project is based on a hypothesis that endogenous host cell poly-(ADPribose) polymerases (PARPs) become activated in bacterial infection and ADP-ribosylate specific host cell proteins to influence pathogen clearance. Mono- and poly-(ADP-ribose)-specific Western blotting was first used to detect ADPribosylated proteins during Salmonella infection and lipopolysaccharide (LPS) or cytokine stimulation of different cell types. Multiple ADP-ribosylated proteins originating either from host cell or the invading Salmonella was detected. It was found that, similarly to Salmonella infection, LPS induced ADP-ribosylation of the host cell proteins. Cytokines did not induce ADP-ribosylation of the host cell proteins. Macrophages displayed more robust changes in ADP-ribosylated proteins as compared to epithelial cells. Secondly, quantitative PCR and Western blotting were used to quantify expression levels of PARPs during Salmonella infection and LPS or cytokine stimulation of different cell types. It was detected one protein to be mono-ADP-ribosylated in both epithelial cells and macrophages. Macrophages showed two additional signals identified as poly-ADP-ribosylation. LPS stimuli in macrophages showed proteins poly-ADP-ribosylated at similar size of one found in bacterial infection. Cytokines did not induce ADP-ribosylation in macrophages. In epithelial cells both LPS and cytokines showed to increase expression of PARP1, while Salmonella had no effect in its expression, whereas in macrophages, PARP1 had different expression by stimuli of bacteria and cytokines but LPS had no effect. As for PARP14 expression in epithelial cells, LPS and TNFα had no effect in its expression however, it showed changes in expression when incubated with the interferons and Salmonella. In macrophages, TNFα remained to have no effect in PARP14 expression while all the other caused differential expression of the enzyme. Lastly, stimulation with bacteria or LPS and IFNγ led to changes in expression values of parp1 and parp14. In conclusion, endogenous host cell PARPs become upregulated, activated and ADPribosylated host cell proteins in Salmonella infection. These changes might benefit the invading bacterium or the human host cells. The results provide the basis for future experimentation on the importance of PARPs and ADP-ribosylation in bacterial infection. This knowledge may allow the development of targeted therapeutic strategies for emerging antibiotic resistant bacteria, potentially involving PARP targeting.